Menopausal Attitude And Symptom In Clımacteric Period Women - Tuğba Dündar; Hilmiye Aksu (Dokuz Eylul University, 2021)
Background: Menopause is a stage within the climacterium, characterized by loss of function of the ovaries and permanent ending of menstruation. Objectives: The aim of this study is to determine the menopausal symptoms, menopausal attitudes and the factors affecting these attitudes of women in the climacteric period. Methods: The universe of the research carried out as a analytical-cross-sectional type was formed 5620 women who applied to Cancer Early Diagnosis, Screening and Education Center, Aydın. The 360 women were included in the sample. Data were collected by interview and self-report method using Assessing Menopausal Symptoms Scale and Attitudes Towards Menopause Scale. In the analysis of the data, descriptive statistics and regression analysis were used. Results: Participants were average 53.07 ± 3.95 years old, 79.7% were menopause. Women were average menopause age of 49.95 ± 1.56, 79.1% of were received information about menopause and 89.1% shared their menopausal complaints with other person. Irritabilty-tension (56%), headache-dizziness (25.6%) and hot flashes-night sweats (24%) were the most complained menopausal symptoms. The mean Attitudes Towards Menopause Scale score of women was determined as 35.24 ± 6.13, and most of participants have a negative attitude. In addition, it was determined that women getting information about menopause (p = .961), go through menopause (p = .324) and the presence of menopausal complaints (p = .311) they experienced did not have a significant affect on the scale score of women. Conclusion: It was found that the attitudes of women towards menopause were mostly negative and the attitude was not affected by some menopausal features of women.